METAL-ORGANIC COMPLEXES IN GEOCHEMICAL PROCESSES: TEMPERATURE DEPENDENCE OF THE STANDARD THERMODYNAMIC PROPERTIES OF AQUEOUS COMPLEXES BETWEEN METAL CATIONS AND DICARBOXYLATE LIGANDS - THEORETICAL MANUAL, USER'S GUIDE, AND RELATED DOCUMENTATION (VERSION 7.0) - Prapaipong P.; Shock E.L.; Koretsky C.M. (My University, 1999)
By combining results from regression and correlation methods, standard state thermodynamic properties for aqueous complexes between metal cations and divalent organic acid ligands (oxalate, malonate, succinate, glutarate, and adipate) are evaluated and applied to geochemical processes. Regression of experimental standard-state equilibrium constants with the revised Helgeson-Kirkham-Flowers (HKF) equation of state yields standard partial molal entropies (S°) of aqueous metal-organic complexes, which allow determination of thermodynamic properties of the complexes at elevated temperatures. In cases where S° is not available from either regression or calorimetric measurement, the values of S° can be estimated from a linear correlation between standard partial molal entropies of association (ΔS^or) and standard partial molal entropies of aqueous cations (S^oM). The correlation is independent of cation charge, which makes it possible to predict S° for complexes between divalent organic acids and numerous metal cations. Similarly, correlations between standard Gibbs free energies of association of metal-organic complexes (ΔG^or) and Gibbs free energies of formation (ΔG^of) for divalent metal cations allow estimates of standard-state equilibrium constants where experimental data are not available. These correlations are found to be a function of ligand structure and cation charge. Predicted equilibrium constants for dicarboxylate complexes of numerous cations were included with those for inorganic and other organic complexes to study the effects of dicarboxylate complexes on the speciation of metals and organic acids in oil-field brines. Relatively low concentrations of oxalic and malonic acids affect the speciation of cations more than similar concentrations of succinic, glutaric, and adipic acids. However, the extent to which metal-dicarboxylate complexes contribute to the speciation of dissolved metals depends on the type of dicarboxylic acid ligand; relative concentration of inorganic, mono-, and dicarboxylate ligands; and the type of metal cation. As an example, in the same solution, dicarboxylic acids have a greater influence on the speciation of Fe+2 and Mg+2 than on the speciation of Zn+2 and Mn+2.